INFLUENCE OF ORGANIZATIONAL CULTURE ON THE QUALITY OF EMPLOYEE PERFORMANCE IN THE ORGANIZATION - Hamsa, Ahmadi; Hayati, Fitri (Indikator Pendidikan Indonesia, 2023)
Organizational culture that is always directed at improving the quality of service as an effort to meet the needs and expectations of society. This study aims to analyze how much influence organizational culture has on employee performance in the organization. This research uses the literature study method in which the researcher collects sources of information from books and journals related to this research. The results of this study are that organizational culture has a significant influence on employee performance in the organization.